Cerebrovascular disease and mortality in hospitalized patients with COVID-19 in a Latin American country, Peru. - Gallo-Guerrero, Marla (2022)
Objective: This study aimed at: 1) Assessment of the frequency of stroke and related mortality rate in patients hospitalized for COVID-19 in two major hospital referral centers in Peru; 2) Exploration of factors associated to mortality and dependency in these patients; 3) Comparisons of frequency of admissions of stroke patients and reperfusion treatments in similar periods of time prior to (2019) and during the pandemia occurrence. Material and Methods: A retrospective cohort study was conducted in two of the largest referral hospital centers for COVID-19 in Peru. The study included patient victims of stroke and COVID-19, hospitalized between April and August 2020. Demographic, clinical and laboratory data, radiological findings, and severity levels measured by the NIHSS scale were collected. Poisson regression models to evaluate associated factors to mortality and dependency were applied. Results: A 31% reduction of admissions for stroke, and of 81% of intravenous reperfusion treatment, respectively, were found in 2020 when compared with 2019. 1.37% of the patients with COVID-19 experienced a stroke, with an overall mortality rate of 40.6%, and a dependency rate of 68.3% at discharge time (Rankin > 2). An age increase of 10 years was found in mortality, associated with a 29% increase in mortality risk. As well, having hypertension, chronic kidney disease, inflammatory markers (D dimer and ferritin) and the severity of the stroke were associated with mortality. Finally, the severity of stroke, lymphopenia, and inflammatory markers (D dimer and fibrinogen) were associated with greater risk of dependency. Conclusions: The care system of stroke patients was affected by the COVID-19 pandemic in two of Perú’s major public hospitals. There was a decrease in admissions and reperfusion treatments of stroke cases, and 1.37% of patients with COVID-19 presented a stroke. Age, hypertension, chronic kidney disease, inflammatory markers and severity of stroke were associated with mortality in these patients.